The Effectiveness of School Program at SDN 21 Taluak, Kecamatan Banuhampu, Kabupaten Agam - Yuhelmi W; Lili Hasmi (International Journal of Social Service and Research, 2023)
The purpose of this research is to describe the effectiveness of school management at SDN 21 Taluak for the 2022/2023 academic year. The management of school activities is the aspects that researched. This research is descriptive qualitative research. The School principal, the teachers, and the committee of SDN 21 Taluak are the subjects. Techniques of collection the data through interviews, observation, and documentation. The data analysis technique that were used are data reduction, data presentation, and drawing conclusions. Credibility test with triangulation of sources and techniques were used to test the validity of the data. The finding showed that: 1) The school management in program planning has been implemented, but the involvement of the parental in the formulation of school plans is still low; 2) The school management in implementing the work plan has been implemented, but there are still program implementations that are not going through the plan; 3) In the terms of leadership the management of the school has been implemented, but the supervision to the principal is still low; 4) The school management in monitoring and evaluation has been carried out, but the program of supervision is still low.